A Review of Statistical Methods for Comparing Two Data Sets - Duffy, A.; Orlandi, A. (Applied Computational Electromagnetics Society Journal (ACES), 2022)
Statistical approaches to compare data for validation of computational electromagnetics have been used for several years. They provide an accepted means of obtaining a numerical value to quantify the data under consideration. However, the use and meaning of these ‘numbers’ depends, by necessity, on the application. This paper provides an overview of some of the most widely applicable techniques, relating the output of these to visual assessment. It further includes comparison with the FSV (Feature Selective Validation) method allowing a triangulation between statistical approaches, visual approaches and heuristic approaches to validation. It is important that the decision to use or reject a particular technique for validation is based on a rational and objective selection approach. This paper suggests a framework to support this selection approach.